Strong influence of the oxygen stoichiometry on the vortex bundle size and critical current densities Jc of GdBa2Cu3Ox-coated conductors grown by co-evaporation. (11th August 2017) - Haberkorn, N; Guimpel, J; Suárez, S; Troiani, H; Granell, P; Golmar, F; Lee, Jae-Hun; Moon, S H; Lee, Hunju
Abstract: We report on the influence of oxygen stoichiometry on the vortex creep mechanism of GdBa2 Cu3 O x -coated conductors produced by co-evaporation. The oxygen stoichiometry of the films, x, was modified in a controlled way between 6.85 and 7, which resulted in systematic and reversible control of the superconducting critical temperature between about 78 and 93 K. The change in the oxygen stoichiometry produces a strong reduction in the self-field critical current densities J c without significantly modifying the power-law dependence at intermediate magnetic fields, which indicates a negligible contribution of oxygen vacancies to the pinning. In addition, the characteristic glassy exponent μ shows a systematic diminution from about 1.63 at x  = 7 to about 1.12 at x  = 6.85. The results are compared with those obtained for proton- and oxygen-irradiated films, in which the vortex dynamics is determined by a balance between the improved pinning, originating from nanocluster inclusion, and the suppressed superconducting properties due to disorder in the nanoscale.